PENILAIAN KINERJA KEUANGAN MENGGUNAKAN METODE MARKET VALUE ADDED (MVA) PADA PERUSAHAAN SEKTOR PERTANIAN DI BURSA EFEK INDONESIA (BEI) PERIODE 2019-2022 - Shalma Nur Fadhila; Zulfa Irawati (Jurnal Ekonomika: Manajemen, Akuntansi, dan Perbankan Syari'ah, 2024)
This study aims to analyze the assessment of financial performance using the market value added (mva) method in agricultural sector companies on the Indonesia Stock Exchange (IDX) for the 2019-2022 period. The type of research used in this research is descriptive with a quantitative approach. The population in this study are companies included in the agricultural sector listed on the IDX and listed on the Indonesia Stock Exchange (IDX) for the 2019-2022 period. Determination of the sample in this study was carried out using purposive sampling method. The data collection method used in this research is documentation. One of the data collection techniques by taking documents to obtain data obtained or collected from various existing sources such as journals, books, financial reports, IDX website, official website of the Indonesia Stock Exchange (IDX), website of each company, and so on made by several companies in the agricultural sector listed on the Indonesia Stock Exchange (IDX). Data analysis stage, obtaining the necessary data from the annual financial statements of agricultural sector companies listed on the Indonesia Stock Exchange (IDX) for the 2019-2022 period and calculating the MVA component. The results of data analysis, namely the value of Market Value Added (MVA) in agricultural sector companies on the Indonesia Stock Exchange (IDX) for the 2019-2022 period have obtained an MVA> 0 value, meaning the company's success in increasing the value of capital invested by funders, in other words the rate of return is greater than capital, so the Market Value Added method can be applied to agricultural sector companies listed on the Indonesia Stock Exchange for the 2019-2022 period.